2015
DOI: 10.1021/acs.accounts.5b00348
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Reactivity and Selectivity in Hydrogen Atom Transfer from Aliphatic C–H Bonds to Alkoxyl Radicals: Role of Structural and Medium Effects

Abstract: Hydrogen atom transfer (HAT) is a fundamental reaction that takes part in a wide variety of chemical and biological processes, with relevant examples that include the action of antioxidants, damage to biomolecules and polymers, and enzymatic and biomimetic reactions. Moreover, great attention is currently devoted to the selective functionalization of unactivated aliphatic C-H bonds, where HAT based procedures have been shown to play an important role. In this Account, we describe the results of our recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
153
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(164 citation statements)
references
References 50 publications
5
153
0
5
Order By: Relevance
“…Selectivity in HAT processes is generally a function of bond strength differential, with the weakest bonds in the substrate being oxidized most rapidly [33]. In fact, such relationships are often presented as evidence for radical-based mechanisms of bond cleavage.…”
Section: Energetic Characteristics Of Pcet Activationmentioning
confidence: 99%
“…Selectivity in HAT processes is generally a function of bond strength differential, with the weakest bonds in the substrate being oxidized most rapidly [33]. In fact, such relationships are often presented as evidence for radical-based mechanisms of bond cleavage.…”
Section: Energetic Characteristics Of Pcet Activationmentioning
confidence: 99%
“…[1] Within this approach, CÀHbonds are regarded as functional groups,and points of potential diversification of al ead structure can be achieved without resorting to de novo synthesis,afeature that makes this strategy particularly useful when applied to drug molecules,natural products,a nd biomolecules. [3][4][5][6] These include bond strengths, electronic or polar effects,c onjugation, hyperconjugation, steric and stereoelectronic effects,torsional effects,aswell as medium effects. [3][4][5][6] These include bond strengths, electronic or polar effects,c onjugation, hyperconjugation, steric and stereoelectronic effects,torsional effects,aswell as medium effects.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Ther eagents that are typically involved in these processes include heteroatomcentered radicals and radical ions,p hotoexcited species and photocatalysts (carbonyl compounds,polyoxometalates), biocatalysts (cytochrome P450 and oxygenases) and bioinspired catalysts,a swell as closed-shell species such as dioxiranes. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Ther eagents that are typically involved in these processes include heteroatomcentered radicals and radical ions,p hotoexcited species and photocatalysts (carbonyl compounds,polyoxometalates), biocatalysts (cytochrome P450 and oxygenases) and bioinspired catalysts,a swell as closed-shell species such as dioxiranes.…”
Section: Introductionmentioning
confidence: 99%
“…Their mildness and functional group tolerance make them particularly attractive for the synthesis of highly functionalized compounds and their reactivity has permitted some unusual transformations. Among all radical reactions, the activation of aliphatic C-H bonds via hydrogen atom transfer (HAT) is a truly unique synthetic tool [3][4][5][6][7]. The preparation of five-membered ring via radical translocationcyclization (RTC) processes involving transient alkenyl radicals proved to be a particularly efficient process [8].…”
mentioning
confidence: 99%
“…Interestingly, Bietti et al have recently demonstrated that the rate of hydrogen atom abstraction from the a-position of tertiary alkylamines by the cumyloxyl radical can be lowered by protonation of the amine (Scheme 3) [5,29]. The authors showed that the rate constant for hydrogen atom abstraction from the a-C-H bonds decreased drastically upon protonation of the nitrogen.…”
mentioning
confidence: 99%